Design, Fabrication and Performance Evaluation of Mixed-Mode Solar Tunnel Dryer for Buffalo Meat by Forced Convection - Paudel, Siddhartha; Dhungana, Bibek (Himalayan Journal of Applied Science and Engineering, 2023)
In the context of Nepal, the consumption, as well as preservation of meat products, has been in practice for ages. The primitive approach - open sun drying technique- a technique for preserving meat for longer, can contaminate the meat. In addition, the meat in direct contact with UV rays also degrades the quality of meat which may not be suitable for consumption. Exposing the meat to the open air causes the evaporation of its moisture, leading to a decline in flavour and an extended duration for the dehydration of the meat product. The alternative technique - mixed mode solar tunnel dryer - is a revolutionary method to undertake the challenges, which uses both solar heated air and direct solar energy. This paper majorly includes the design, fabrication and performance evaluation of a solar mixed-mode tunnel dryer by forced convection for buffalo meat. The purposed system was designed for drying 4 kg of meat for humid sub-tropical climatic conditions with an estimated design drying time of 7 hrs 44 mins. The designed system includes a collector of area 2 m2, a drying chamber, and a DC fan. The recorded parameters were incident solar irradiance, air temperature, relative humidity of the air, and moisture content of meat at equal intervals. Reducing the moisture content in buffalo meat to 26.78% by weight in the month of November, took a total of 14 hrs with maximum collector efficiency of 29.79%.